Comparing the Performance of Digital Rectal Examination and Prostate-specific Antigen as a Screening Test for Prostate Cancer: A Systematic Review and Meta-analysis - Matsukawa, Akihiro; Yanagisawa, Takafumi; Bekku, Kensuke; Kardoust Parizi, Mehdi; Laukhtina, Ekaterina; Klemm, Jakob; Chiujdea, Sever; Mori, Keiichiro; Kimura, Shoji; Fazekas, Tamas; Miszczyk, Marcin; Miki, Jun; et al. (European urology oncology, 2024)
BACKGROUND AND OBJECTIVE: Although digital rectal examination (DRE) is recommended in combination with prostate-specific antigen (PSA) for detection of prostate cancer (PCa), there are limited data to support its use as a screening/early detection test. Our objective was to assess the diagnostic value of DRE in screening for early detection of PCa. METHODS: In August 2023, we queried the PubMed, Scopus, and Web of Science databases to identify prospective studies simultaneously investigating the diagnostic performance of DRE and PSA for PCa screening. The primary endpoints were the positive predictive value (PPV) and cancer detection rate (CDR) of DRE. Secondary endpoints included the PPV and CDR of both PSA alone and in combination with DRE. We conducted meta-regression analysis to compare the CDR and PPV of different screening strategies. This meta-analysis is registered on PROSPERO (CRD42023446940). KEY FINDINGS AND LIMITATIONS: We identified eight studies involving 85,798 participants, of which three were randomized controlled trials and five were prospective diagnostic studies, that reported the PPV and CDR of both DRE and PSA for the same cohort. Our analysis revealed a pooled PPV of 0.21 (95% confidence interval [CI] 0.13-0.33) for DRE, which is similar to the PPV of PSA (0.22, 95% CI 0.15-0.30; p = 0.9), with no benefit from combining DRE and PSA (PPV 0.19, 95% CI 0.13-0.26; p = 0.5). However, the CDR of DRE (0.01, 95% CI: 0.01-0.02) was significantly lower than that of PSA (0.03, 95% CI 0.02-0.03; p < 0.05) and the combination of DRE and PSA (0.03, 95% CI 0.02-0.04; p < 0.05). The screening strategy combining DRE and PSA was not different to that of PSA alone in terms of CDR (p = 0.5) and PPV (p = 0.5). CONCLUSIONS AND CLINICAL IMPLICATIONS: Our comprehensive review and meta-analysis indicates that both as an independent test and as a supplementary measure to PSA for PCa detection, DRE exhibits a notably low diagnostic value. The collective findings from the included studies suggest that, in the absence of clinical symptoms and signs, DRE could be potentially omitted from PCa screening and early detection strategies. PATIENT SUMMARY: Our review shows that the screening performance of digital rectal examination for detection of prostate cancer is not particularly impressive, suggesting that it might not be necessary to conduct this examination routinely.
Keywords: Prostatic Neoplasms; časná detekce nádoru; nádory prostaty; palpační vyšetření konečníku; Prostate-Specific Antigen; Humans; Early Detection of Cancer; mužské pohlaví; Male; lidé; prostatický specifický antigen; Digital Rectal Examination